Effectiveness of Psychospiritual Awareness Training and Butterfly Hug Technique on Emotional Regulation of Grade VI Elementary School - Muhammad Adfan Madji; Nasywa Nabillah; Lusiana Dwi Puspita; Nabilla Rosydah; Magita Salsabilla; Herliyana Isnaeni (PT. TAROMBO RESEARCH DEVELOPMENT pak, 2026)
Social changes and academic demands on final-year elementary school students often trigger emotional challenges that are not balanced with adequate mental health assistance. This study aims to examine the effectiveness of the training program